Assessment of the Health Level of Rural Banks (BPR) in Buleleng Regency during the Covid-19 Pandemic - Putu Riesty Masdiantini; Ni Luh Asri Savitri; Sunitha Devi; Putu Eka Dianita Marvilianti Dewi (Universitas Pendidikan Ganesha, 2023)
This study aims to determine the health level of Rural Banks (BPR) during the Covid-19 pandemic, especially BPRs in Buleleng Regency registered with the Financial Services Authority (OJK) with the RGEC method. The research method used is descriptive research with a quantitative approach. This study used a sample of rural banks in Buleleng Regency. The data used is secondary data obtained from BPR financial reports published on the OJK website. The results showed that the health level of BPRs in Buleleng Regency was in a fairly healthy predicate in the first and third Quarters of 2020, which was when the Covid-19 Pandemic condition was announced in Indonesia so that it had a shock effect on the performance of BPRs. However, BPR can immediately overcome this condition by following various government policies, so that it becomes a healthy predicate in the second, third and fourth quarters of 2021. Keywords: Bank soundness level, rural banks, Covid-19 pandemic